Tax benefits as a key motive for creating a tax capital group in Poland - Toborek- Mazur, Joanna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The paper addresses the issues of factors determining the functioning of tax capital groups in Poland. The author points out the most important motivators from the point of view of organizing group of companies, but also the reasons for establishing and legal basis for forming tax capital groups. Based on the tax capital group of one of the largest insurance companies in Poland - PZU. Additionally, the author analyzed the method of creating a tax capital group and presented the most important benefits obtained by the tax entity. The validity of the decision taken within the capital group can be assessed in the areas of: accounting, tax settlements, fulfilling other tax duties and principles of cooperating in PGK PZU. As a result of the analysis, a new trend was identified related to the creation of tax unity in Poland.